The Influence of Brainstorming Method Through “Good Collaboration” Stories to Improve the Critical Thinking Dimension of Elementary School Students - Barokah Khasanah, Sahrul; Puspita, Yenny; Faipri Selegi, Susanti (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2025)
Indonesian Language Learning is a learning that has an important role in developing students' critical thinking skills. In fact, the critical thinking ability of students in class IV of SD Negeri 80 Palembang in learning Indonesian is still classified as low. The purpose of this research is to find out the influence of the brainstorming method through the story